DUKUNGAN KESEHATAN JIWA DAN PSIKOSOSIAL DI MASA PANDEMI COVID-19 PADA KADER KESEHATAN DAN MASYARAKAT MELALUI ZOOM MEETING - Tanti Suryawantie; Iin Patimah; Santi; Desti; Siti Rahmalia; Fitriana, Fitriana (LP4M STIKes Karsa Husada Garut, 2021)
Health cadres are members of the community whose role is to assist health workers in health services. For the case of the Covid-19 pandemic, especially health cadres who are needed to assist the community in handling mental and psychosocial health in the community. In addition to health cadres, the general public also plays a role in helping cadres and health workers to improve the mental health of the community. One of the efforts is to increase knowledge through health counseling about mental health during the COVID-19 pandemic. Health counseling was carried out boldly in their respective homes with zoom media on July 18, 2021. There were 24 participants who took part in the health education, consisting of 14 health cadres and 10 the general public. Beforethe counseling was carried out, pre-test and post-test were carried out by distributing questionnaires on google forms to participants to determine the level of knowledge of the participants about the material to be and after being delivered. This community service activity succeeded in increasing the knowledge of health cadres and the community about psychosocial mental health support with the value of good knowledge being 36% from 18%, and knowledge being 64% from 45%. After this community service is held, it is hoped that the participants can become promoters in mental health efforts in the community during the Covid-19 pandemic so that they can remain mentally healthy in dealing with all the problems that occur during this COVID-19 pandemic.